The association between blood pressure and serum cholesterol in healthy men: the Oslo study. Issue 2 (June 1978) - Hjermann, I; Helgeland, A; Holme, I; Lund-Larsen, P G; Leren, P
Abstract : The association between serum cholesterol and blood pressure (BP) has been studied in 16 525 men. The study reveals that these Oslo men in their forties present with a serum cholesterol value which is on average 0.71 mmol/l (27.4 mg/100 ml) higher at diastolic BP greater than 110 mmHg than at BP less than 70 mmHg. According to earlier studies in Oslo, this cholesterol difference alone imparts a 10-year myocardial infarction morbidity difference of 25–30%. These findings might be of practical importance for epidemiological studies and for preventive measures against the two factors. The influence of other variables on the association between blood pressure and cholesterol has been studied in a multivariate analysis. Of these variables, only body mass index and serum triglycerides significantly influence the relationship between blood pressure and cholesterol, whereas age, cigarette smoking, non-fasting blood sugar, season, socioeconomic status, and physical activity at work and leisure do not influence the correlation.